The effect of beetroot juice supplementation on dynamic apnea and intermittent sprint performance in elite female water polo players - Jonvik ,K. L.; van Dijk, J.-W.; Senden, J. M. G.; van Loon, L. J. C.; Verdijk, L. B. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
Nitrate-rich beetroot juice is thought to have ergogenic effects, particularly in conditions where oxygen availability is limited. Whether these effects also apply to elite athletes is currently unknown. The aim of this study was to assess the effects of beetroot juice supplementation on dynamic apnea and intermittent sprint performance in elite female water polo players. In a double-blinded, randomized, crossover manner, the Dutch National female water polo team (N = 14) was subjected to two 6-day supplementation periods (1 and 2), with either 140 ml/day of nitrate-rich (BR; ~800 mg/day nitrate) or nitrate-depleted (PLA) beetroot juice. Following blood sampling on Day 6, the athletes performed a maximal-distance front crawl swimming test without breathing (dynamic apnea test). In addition, intermittent sprint performance was assessed by performing 16 swim sprints of 15 m, in a 4 × 4 block with 30-s recovery between blocks (intermittent test). Distance covered during the dynamic apnea test did not differ between BR (49.5 ± 7.8 m) and PLA (46.9 ± 9.1 m, p = .178). However, when correcting for test order, the distance covered was significantly larger in BR versus PLA when BR was ingested in Period 2 (50.1 ± 8.5 vs. 42.8 ± 5.7 m, p = .002), whereas no difference was observed when BR was ingested in Period 1 (48.8 ± 7.4 vs. 52.3 ± 10.4 m, p = .10). The time to complete the intermittent test was not different between BR and PLA (316.0 ± 7.9 vs. 316.3 ± 6.9 s, p = .73). In conclusion, beetroot juice supplementation does not improve intermittent performance in elite female water polo players, but there may be a potential for ergogenic effects during dynamic apnea.